Specific measures for older employees and late career employment - Bernhard Boockmann; Jan Fries; Christian Göbel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We analyse the effects of specific measures for older employees (SMOE) on employment duration of workers aged 40 and above. Using longitudinal employer-employee data for German establishments, we account for worker and establishment heterogeneity and correct for stock-sampling. We find a positive effect of mixed-aged team work on employment duration and a negative effect of a part-time scheme addressed at older workers. Employment duration does not appear to be related to other SMOE, such as training and specific equipment of workplaces.
Keywords: J14; J21; J26; 330; older workers; human resources policies; SMOE; employment duration; linked employer-employee data; age; tenure